Tin powder promoted synthesis of trifluoroethylamine‐containing 3, 3′‐disubstituted oxindoles. (23rd May 2019) - Wang, Xiaoping; Huang, Danfeng; Wang, Ke‐Hu; Liu, Jiaxin; Zong, Wuzhong; Wang, Juanjuan; Su, Yingpeng; Hu, Yulai
Abstract : An efficient and facile approach for the construction of trifluoroethylamine‐containing 3, 3′‐disubstituted oxindoles or 3‐spirooxindoles is developed through the reaction of isatins, 2, 2, 2‐trifluoroethylamine hydrochloride and allyl bromides or 2‐(bromomethyl)acrylic ester mediated by tin powder. This method uses simple and commercially available 2, 2, 2‐trifluoroethylamine hydrochloride as a trifluoroethylamine building block and avoids the use of toxic allylstannanes. Abstract : Trifluoroethylamine‐containing 3, 3′‐disubstituted/spirocyclic oxindoles were synthesized by isatins, 2, 2, 2‐trifluoroethylamine hydrochloride and allyl bromides or 2‐(bromomethyl)acrylic ester. The process underwent tin powder promoted tandem C − C and C − N bond formation, producing oxindole derivatives in good to excellent yields.